2010
DOI: 10.1021/jp1061623
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Environment of the S2State of Photosystem II: A Study of the Hyperfine Interactions of the Tetranuclear Manganese Cluster by 2D14N HYSCORE Spectroscopy

Abstract: The solar water-splitting protein complex, photosystem II, catalyzes the light-driven oxidation of water to dioxygen in Nature. The four-electron oxidation reaction of water occurs at the tetranuclear manganese-calcium-oxo catalytic cluster that is present in the oxygen-evolving complex of photosystem II. The mechanism of light-driven water oxidation has been a subject of intense interest, and the oxygen-evolving complex of photosystem II has been studied extensively by structural and biochemical methods. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
136
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(149 citation statements)
references
References 45 publications
13
136
0
Order By: Relevance
“…Comparing this structure with the S 2 model [262] predicts that the dangler Mn is oxidized forming S 2 and one of the waters attached to this Mn looses a proton to become a hydroxyl. This assignment for the Mn oxidation agrees with recent HYSCORE experiments [264]. Consistent with the S 1 structure, all of the bridging oxygens are deprotonated.…”
Section: Mechanism Of Proton Binding and Release That Generate Thesupporting
confidence: 89%
“…Comparing this structure with the S 2 model [262] predicts that the dangler Mn is oxidized forming S 2 and one of the waters attached to this Mn looses a proton to become a hydroxyl. This assignment for the Mn oxidation agrees with recent HYSCORE experiments [264]. Consistent with the S 1 structure, all of the bridging oxygens are deprotonated.…”
Section: Mechanism Of Proton Binding and Release That Generate Thesupporting
confidence: 89%
“…PCC 6803 found that the 4.8 MHz peak decreased or disappeared upon this mutation (see Figure S1). (40) A similar feature has now been observed in X -band ESEEM spectra of PSII isolated from higher plants (spinach(4042) and pea seedlings(43)) as well as mesophilic(38,40) and thermophilic cyanobacteria. (36) Unfortunately, rather little information as to the strength of the magnetic interaction between this histidine nitrogen and the OEC can be derived from just one peak.…”
supporting
confidence: 61%
“…In the present study, we use two-dimensional (2D) hyperfine sublevel correlation (HYSCORE) spectroscopy (see Transparent Methods) to obtain a quantitative measure of the hyperfine and quadrupolar parameters of the BiP-PF 10 ,+ radical (Chatterjee et al, 2013(Chatterjee et al, , 2012Coates et al, 2015;Dikanov et al, 2019Dikanov et al, , 2000Dikanov and Taguchi, 2018;Hö fer et al, 1986;Milikisiyants et al, 2011Milikisiyants et al, , 2010. 2D HYSCORE spectroscopy is similar to the pulsed EPR spectroscopy methods, electron nuclear double resonance (ENDOR), and electron spin echo envelope modulation (ESEEM) (Britt, 2003;Deligiannakis et al, 2000;Harmer et al, 2009;Lakshmi and Brudvig, 2001;Prisner et al, 2001), that are used for the study of electron-nuclear hyperfine interactions in paramagnetic systems.…”
Section: Resultsmentioning
confidence: 99%